Outcomes of Endoscopic Myringoplasty (Med Phoenix, 2022)
Introduction: The endoscope has diagnostic and therapeutic role in different otological surgeries. It has excellent view of images where there are difficult nooks and corners. The use of tragal cartilage in the repair of tympanic membrane perforation has its own benefit in graft uptake and hearing results whether long term or short term. The main purpose of the present study was to evaluate the long‑term hearing results in patients who underwent endoscopic sandwich myringoplasty with National Medical college & Teaching Hospital, Birgunj.Objective: To evaluate the graft success rate and postoperative hearing gain for central perforations using endoscopic myringoplastyMaterials and Methods: This study is a prospective study in 60 patients with central perforations who underwent endoscopic myringoplasty using tragal cartilage. The hearing was assessed by comparing pre‑. with post‑operative air‑bone gap (ABG) and ABG closure in speech frequencies (0.5 kHz, 1 kHz, 2 kHz, and 4 KHz).Results: Of the 60 patients with central perforation included in this study, the graft success rate was 95% (57/60). The graft uptake in 6 months of follow‑up. The postoperative ABG (13.77 ± 4.94dB) was lesser than preoperative ABG (22.38 ± 6.93 dB) with statistically significant results.Conclusion: Endoscopic myringoplasty is a safe procedure with high‑graft uptake rate and good long‑term hearing results.